Advertising and Public Relations Professional Education in the Regions of Russia: Educational Organizations Branding Issues - L. V. Sharakhina; A. V. Ranchin (Дискурс, 2020)
Introduction. The Russian higher education market in the sphere of Public Relations and Advertising is represented in the paper. The basic approach to the market is shaped by the vision on higher education in the frame of service paradigm. The need to analyze and implement professional communication activities while promoting university education organizations is stressed by the authors. A special attention is put to the necessity of professional communication technologies, such as branding, their application to universities, because it influence such institutions managerial efficiency, helps to systemize a share of their voice, and it is already the necessity for the present day society.Methodology and sources. Theoretical and methodological basis of the paper was composed by scientific works of Russian researchers in the field of university branding, brand-management, including papers on Russian Federation regional universities branding. Empirical study base was designed by materials of regional leading universities, which give higher education in PR and Advertising. Underlying rationale for defining the leadership were the following: number of state-funded student places; 1st year students’ unified national exam results; the dynamics of prospective students in PR and Advertising on tuition payment basis enrollment. Russian regions, the most of enrollees are coming from to Saint Petersburg Electrotechnical University, were also unveiled. The elements of value-based branding platforms of departments responsible for Public Relations and Advertising education in regional leading higher education institutions are also brought in focus.Results and discussion. Empirical study revealed that PR and Advertising education departments of the universities studied did not fulfill their scientific and methodological potential in practice to the full extent. The education institutions examined in the research mostly communicate their objective quantitative indicators positioning Public Relations and Advertising education rather than core value messages. Thus it does not seem possible to typify these communication components as examples of branding process and brand element of university. It would help to structure the market share and influence positively on university promotion.Conclusion. Following the results of the study the authors conclude the necessity to apply communication technologies of brand development and brand management for structuring the market share and influencing positively on university promotion. It directly impacts on education institutions managerial efficiency and proves its relevance to modern society.